2017
DOI: 10.23907/2017.012
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin in Mixed Drug Fatalities: Does this Frequent Analyte Deserve More Attention?

Abstract: From 2000 to 2014, drug overdose deaths increased 137% in the United States, and 61% of these deaths included some form of opiate. The vast majority of opiate-related drug fatalities include multiple drugs, although there is scant data quantitatively describing the exact drugs that contribute to deaths due to multiple drugs. In the present study, we sought to quantitatively identify the drugs that occur with opiates in accidental multidrug-related fatalities. We retrospectively explored fatal drug trends in fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…One mass spectrometer instrument manufacturer has an application note for quantitative analysis of 65 drugs and metabolites on a triple quadrupole mass spectrometer, but the limits are truncated as the highest calibrator investigated was 1000 ng/mL (36). This would prove untenable for many of the analytes listed here as their concentrations are typically much higher than 1000 ng/mL on average in patients (14)(15)(16)(17)(18). To our knowledge this is the first publication of a time-efficient and comprehensive quantitative method that describes in depth these considerations when developing and validating the method.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…One mass spectrometer instrument manufacturer has an application note for quantitative analysis of 65 drugs and metabolites on a triple quadrupole mass spectrometer, but the limits are truncated as the highest calibrator investigated was 1000 ng/mL (36). This would prove untenable for many of the analytes listed here as their concentrations are typically much higher than 1000 ng/mL on average in patients (14)(15)(16)(17)(18). To our knowledge this is the first publication of a time-efficient and comprehensive quantitative method that describes in depth these considerations when developing and validating the method.…”
Section: Discussionmentioning
confidence: 98%
“…This assay was designed around these expectations to capture the most commonly requested assays, except for analytes/assays that require relatively low concentration ranges, which were left out because the dynamic range restrictions of LC-MS/MS made their inclusion problematic. This is not to say that LC-MS/MS cannot analyze very low concentrations, rather that the combination of low limits of quantification (LOQ) 2 with very high upper limits of quantification (ULOQ) as required by opiates and opioids (14)(15)(16)(17)(18) requires a large dynamic range, which is often untenable.…”
mentioning
confidence: 99%
“…Concomitant use with opioids significantly increases the risk of fatal opioid overdose, especially at high gabapentin doses, likely due to exacerbated respiratory depression 6 . A study of accidental mixed drug fatalities involving opioids found gabapentin to be present in 26% of cases and typically within normal therapeutic dose ranges 22 …”
Section: Introductionmentioning
confidence: 99%
“… 6 A study of accidental mixed drug fatalities involving opioids found gabapentin to be present in 26% of cases and typically within normal therapeutic dose ranges. 22 …”
Section: Introductionmentioning
confidence: 99%
“…Gabapentin can be used to potentiate illicit opioids; data indicate gabapentin exposures associated with intentional abuse, misuse, or unknown exposures reported to U.S. poison centers increased by 104% from 2013 to 2017 ( 3 ). However, less is known about the drug’s role in fatal overdoses ( 4 ). To assess quarterly trends in gabapentin-involved overdose deaths of unintentional or undetermined intent during 2019 – 2020, CDC analyzed data from the State Unintentional Drug Overdose Reporting System (SUDORS) in 23 states and the District of Columbia.…”
mentioning
confidence: 99%